Evaluation of users' privacy concerns by checking of their WhatsApp status. (1st February 2018) - Malekhosseini, Razieh; Hosseinzadeh, Mehdi; Navi, Keyvan
Summary: WhatsApp Messenger is a popular instant messenger among Iranian users. The WhatsApp status feature provides the possibility of posting desired content without restrictions in terms of type with the capability of being managed by users. Status can be considered as a potential place to express users' feelings, opinions, and thoughts. However, special attention should be paid to the privacy of users and the information published in this manner because access to the content of a user's status by unauthorized friends and interpretations of the user's status content may violate his/her privacy. This study investigates the privacy issues associated with information shared through status. The data of this study were gathered via access to the status content of 4000 Iranian users and via telephone interviews conducted with 350 of them. In this study, a combination of quantitative and qualitative methods has been used to analyze the data. This study focuses on the extraction of patterns in users' status content, determination of their polarity, and examination of the factors affecting users' privacy concerns. During the research, 10 general themes were extracted from users' content. The results showed that user privacy concerns influenced the type of theme selected. In addition, the theme selected under different circumstances may include a type of feeling that, in this study, is called polarity. Polarity is affected by the users' privacy concerns. Moreover, the demographic characteristics of users (age and gender) have a significant relationship with the type of theme used and their privacy concerns.